Cesium desorption behavior of weathered biotite in Fukushima considering the actual radioactive contamination level of soils. (October 2018) - Mukai, Hiroki; Tamura, Kenji; Kikuchi, Ryosuke; Takahashi, Yoshio; Yaita, Tsuyoshi; Kogure, Toshihiro
Abstract: For the better understanding of radioactive contamination in Fukushima Prefecture at present and in future, Cs desorption experiments have been conducted mainly using weathered biotite (WB) collected from Fukushima Prefecture and considering the actual contamination level (∼10 −10  wt%) of radiocesium in Fukushima Prefecture. In the experiments, 137 Cs sorbed to WB by immersing in 137 Cs solution for one day was mostly desorbed by solutions of 1 M NaNO3, 1 M LiNO3, 10 −1  M HCl, and 10 −1  M HNO3, although it was barely desorbed by 1 M KNO3, 1 M CsNO3, 1 M NH4 NO3, and natural seawater. X-ray diffraction analysis of WB after immersing in these solutions suggested that the collapse of the hydrated interlayers in WB suppressed the desorption of Cs. On the other hand, 137 Cs was barely desorbed from WB even by the treatments with solutions of NaNO3 and LiNO3 if the duration for the sorption was longer than approximately two weeks, as well as radioactive WB collected from actual contaminated soils in Fukushima Prefecture. This result implies that Cs sorbed in WB became more strongly fixed with time. Probably removal of radiocesium sorbed in weathered granitic soil at Fukushima Prefecture is difficult by any electrolyte solutions, as more than seven years have passed since the accident. Graphical abstract: Image 1 Highlights: Cs desorption property of Fukushima weathered biotite (WB) was investigated. Cs concentration was set very low, to simulate actual contamination in Fukushima. Cs sorbed to WB was not desorbed by seawater due to the presence of K + . The desorption behavior was strongly dependent on the period for sorption. Partial dissolution of the host mineral was necessary to release Cs efficiently.